The Performance Analysis of Horticultural Farmer Groups in Tampa Bulu Village North Poleang Sub-District Bombana District - Sulaiman Sulaiman; Marsuki iswandi; La Ode Alwi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This study aims to determine the performance and role of horticultural farmer groups in Tampa Bulu Village, North Poleang Sub-district, Bombana District, Southeast Sulawesi. Through this research, it is expected that strategies can be found to improve the effectiveness and efficiency of farmer groups in developing horticultural farming. This research was conducted from June 2022 to May 2023. The research location was chosen purposively because it has four horticultural farmer groups with 30 members each formed since 2016. The study population was all members of horticultural farmer groups in Tampa Bulu Village, totaling 120 people. The sample was taken randomly using the Taro Yamane formula with a margin of error of 15%, resulting in a sample of 32 people. The variables studied included the characteristics of respondents (age, education, land area, and length of farming) and the performance of farmer groups assessed by their role as a learning class, a vehicle for cooperation, and a production unit. The analytical tool used is Importance Performance Analysis (IPA), which measures the level of importance and performance in a two-dimensional graph. The results showed that most respondents were in the productive age range of 15-54 years (90.63%) with an education level of primarily high school graduates (43.76%). 81.25% of respondents had more than ten years of farming experience, and 50% had less than four dependents. Based on IPA analysis, six attributes were found in the